What factors determine the fastest start performance in front crawl swimming - Takeda, T.; Okuno, K. (Sport Science Research, 2014)
The purpose of this study was to investigate correlation between 15 m time and kinematic variables in 25 m sprint by front crawl swimming. Twelve college male swimmers participated in this study. Their swimming performance ranged national to international levels. The participants swam 25 m sprint swimming three times by front crawl with maximum effort. Four video cameras were placed on the poolside deck and under water to record swimming motion. The elapsed times at taking off from the start block, 15 m and 25 m were measured by counting the number of the video frames. Two-dimensional co-ordinates during motion were obtained from the video images using direct linear transformation methods. Pearson`s correlation coefficients were calculated between 15 m time and the variables (block time, horizontal take off velocity, take off angle, flight distance, entry angle, start depth). Flight distance strongly correlated with 15 m time (r = 0.74, P < 0.01). Coefficients of correlation ® in horizontal take off velocity and block time were -0.51 (P > 0.05) and 0.52 (P > 0.05), respectively. We suggested that long flight distance and water-entry with low water resistance were key factors for successful swimming start in front crawl.